The use of the individual development plan at minority serving institutions - Chang, Chi-Ning; Justus-Smith, Cammie; Malagon-Palacios, Laura J.; Hui, John (Frontiers in Education, 2023)
The Individual Development Plan (IDP) is a common mentoring tool in higher education. Students and postdoctoral researchers can use an IDP to facilitate conversations with their mentors and create action plans to support future goals. The entire process helps mentees achieve both short- and long-term objectives. Little is known about how historically underrepresented minority groups are supported during this process. This study investigated IDP implementation at 504 minority serving institutions (MSIs) that primarily serve African American, Hispanic/Latinx, and Native-American populations. Using content analysis, we systematically reviewed the publicly available IDP tools and policies at each MSI. Although several crucial mentoring components and implementation strategies were identified, there was a noticeable absence of emphasis on multicultural mentoring guidance and psychosocial support throughout the process. Our findings offer decision-makers and faculty mentors insights into supporting minority trainees and lay the foundation for future research in the field of IDPs.